Are the Humanities No Longer Relevant in the 21st Century? The case of Israel – Supply and demand for the humanities in Israel’s academic institutions: Between academic policy and “market forces” - Davidovitch, Nitza (Journal of Education Culture and Society, 2020)
Aims. In view of the diminishing demand for the humanities in Israel, we explore the profiles of current students of humanities in one high school and one university in Israel. Method. This study reviews the changes in the demand for and status of academic humanities studies and maps the profile of students of the humanities, both high school students and high school graduates over the age of 18. In total, 136 students (73 males and 60 females) participated in this survey-based study Results and Conclusion. The results show a positive and significant correlation between attitudes regarding the humanities and motivation to study these subjects in the future. In addition, a positive correlation was found between values of honesty, helping others, and contribution to the country, and motivation to study the humanities. Contribution. The findings of this study contribute by daring to challenge the perception concerning the insignificant status of the humanities in our day and age – aimed at eliminating them and rendering them irrelevant.